The participation in the construction of political spaces by the umbandists in the municipality of the Rio de Janeiro: visibility, recognition and political representativeness - Morais, Marcelo Alonso (Geografares, 2018)
In the Municipality of Rio de Janeiro, increasing religious intolerance, the difficulty of access to public spaces and the maintenance of private spaces, and the need for adaptation of religions to the Brazilian Constitution, have led Umbandist groups to participate and / or to build political spaces and , consequently, public agendas that take into account the material and immaterial demands of the populations involved, thus creating spatial conditions that allow visibility and effectiveness of decisions in a democratic context. Thus, the article seeks to bring to light a reflection on how political spaces are part of the Umbandist groups’ strategies in the exercise of citizenship in the city of Rio de Janeiro.Keywords: Space - Politics - Religion - Citizenship.